Historical and legal aspects of development of the banking system in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
The article deals with the historical aspects of the banking system, institutional reforms of financial control andsupervision. Briefly analyzes the development and establishment of law in the banking sector.Key words: banking, commercial banks, National Bank, legislation, monetary policy, deposits ipoteny contribution,the national currency (Tenge).